2021
DOI: 10.1016/j.annonc.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Bamlanivimab + etesevimab therapy induces SARS-CoV-2 immune escape mutations and secondary clinical deterioration in COVID-19 patients with B-cell malignancies

Abstract: Bamlivimab + etesevimab therapy induces SARS-COV-2 immune escape mutations and secondary clinical deterioration in Covid-19 patients with B cell malignancies F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…The Alpha variant is refractory to neutralization by most mAbs, which target the NTD of Spike protein and also resistant to several RBD-specific mAbs (9). Mutations in the Beta lineage (K417N, E484K, and N501Y in RBD), especially mutations of Spike at E484 but also in the Nterminal domain (NTD; L18F, D80A, D215G, D242-244, and R246I in SA variant (10,11)), reduce neutralization sensitivity or confer neutralization escape from multiple mAbs (4,5,(12)(13)(14)(15)(16)(17)(18)(19)(20). Third, polyclonal antibodies produced in their Fab'2 format from horses (21) or in their IgG format from humanized cows (22) or glyco-humanized pigs (23) have also proven efficacy to neutralize SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The Alpha variant is refractory to neutralization by most mAbs, which target the NTD of Spike protein and also resistant to several RBD-specific mAbs (9). Mutations in the Beta lineage (K417N, E484K, and N501Y in RBD), especially mutations of Spike at E484 but also in the Nterminal domain (NTD; L18F, D80A, D215G, D242-244, and R246I in SA variant (10,11)), reduce neutralization sensitivity or confer neutralization escape from multiple mAbs (4,5,(12)(13)(14)(15)(16)(17)(18)(19)(20). Third, polyclonal antibodies produced in their Fab'2 format from horses (21) or in their IgG format from humanized cows (22) or glyco-humanized pigs (23) have also proven efficacy to neutralize SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Although the BLAZE-1 trial showed that both monotherapy with bamlanivimab and combination therapy with bamlanivimab and etesevimab reduced the risk of hospitalization and COVID-19 progression compared to a placebo group [8], some concerns remain over the risk of mutation emergence in the S gene under selective pressure from monotherapy with bamlanivimab [9]. Some cases of Q493R mutations following bamlanivimab/etesevimab administration were also reported in the literature and are associated with a reduced viral clearance and, in some patients, with fatal outcome [10][11][12][13].…”
Section: Introductionmentioning
confidence: 95%
“…in low and middle income countries) 4 , scarce, or ineffective (i.e. in the context of mAb-resistant variants) 5 . COVID-19 convalescent plasma (CCP) is safe in hospitalized populations 6,7 .…”
Section: Introductionmentioning
confidence: 99%